Unraveling Complex Water Industry Issues Is No Easy Task. Issue 10 (2nd October 2018) - Flancher, Dawn
Abstract : This is AWWA's 15th year conducting the State of the Water Industry (SOTWI) survey. Water industry professionals have provided a wealth of perspective on the issues of immediate and growing concern to the water industry.